A new record of Formosaneleotris hualienensis (Gobioidei), from the Solomon Islands - Larson, Helen K.; Boseto, David; Jenkins, Aaron; Chen, I-Shiung (Zootaxa, 2025)
The obscure and poorly-known eleotrid Formosaneleotris hualienensis is recorded from the Solomon Islands, with colour photographs, and notes on its habitat. Information on a second record of this species from Taiwan is also provided.